Factors Influence Cloud Computing Assimilation and the Effect to IT Operational Effectiveness in Public Sector - Sallehudin, Hasimi; Che Razak, Razli; Ismail, Mohammad (School of Social Sciences, 2015)
The role of IT innovation has changed from conventional cost reduction and efficiency improvement to enhancement of public sector agency’s flexibility and adaptation to changing environment. However, a comprehensive literature review reveals that there is a lack of study of which reasons persuade the public sector to implement information technology (IT) innovation, as well as which factor and how affect the level of IT sophistication in this assimilation process and the effect to the operational effectiveness. Based on Diffusion Innovation Theory (DOI), and Technology-Organizational-Environmental framework (TOE), nine determinant are proposed to influence cloud computing assimilation. A measurement scale is developed by adopting from prior empirical studies and the context of cloud-based resources and services implementation in the Malaysian public sector were tested and evaluated using survey data from a sample of 169 agencies. Our empirical analyses lead to several key findings; Technological factor is significantly affects the relationship to cloud-based services and resources Initiation and Implementation by the agencies in the Malaysian public sector. Organizational factors significantly affects cloud-based services and resources initiation, but not significantly support the relationship to its implementation. However, Environmental factors significantly affects cloud-based services and resources implementation, but not significantly support the relationship to its initiation. Initiation to cloud-based services and resources by the agencies in the Malaysian public sector is not significantly support its implementation. The Implementation of cloud-based services and resources by the agencies in the Malaysian public sector significantly affect IT operational effectiveness.